2021
DOI: 10.3389/fcell.2021.670882
|View full text |Cite
|
Sign up to set email alerts
|

F-Actin Dynamics in the Regulation of Endosomal Recycling and Immune Synapse Assembly

Abstract: Membrane proteins endocytosed at the cell surface as vesicular cargoes are sorted at early endosomes for delivery to lysosomes for degradation or alternatively recycled to different cellular destinations. Cargo recycling is orchestrated by multimolecular complexes that include the retromer, retriever, and the WASH complex, which promote the polymerization of new actin filaments at early endosomes. These endosomal actin pools play a key role at different steps of the recycling process, from cargo segregation to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 149 publications
(204 reference statements)
2
2
0
Order By: Relevance
“…Given that LegK2 is detected on the LCV surface 1 h post-infection 16 and that VipA-derived peptides were identified at the LCV 1 h postinfection 38 , it can be hypothesized that the antagonistic activities of the LegK2/VipA effector pair can temporally control actin polymerization on the LCV to interfere with phagosome maturation and endosome recycling. Indeed, the actin polymerization inhibition activity exerted by LegK2, followed by the actin polymerization activity exerted by VipA, would be consistent with the well-established observation that, after bacterial engulfment, actin and associated proteins dissembles but are recruited again at a later stage of endocytic transit 30,53,54 . In addition to directly controlling actin polymerization, L. pneumophila also controls actin degradation at the LCV 55 and secretes RavK, an actin-targeting effector protease.…”
Section: Discussionsupporting
confidence: 87%
“…Given that LegK2 is detected on the LCV surface 1 h post-infection 16 and that VipA-derived peptides were identified at the LCV 1 h postinfection 38 , it can be hypothesized that the antagonistic activities of the LegK2/VipA effector pair can temporally control actin polymerization on the LCV to interfere with phagosome maturation and endosome recycling. Indeed, the actin polymerization inhibition activity exerted by LegK2, followed by the actin polymerization activity exerted by VipA, would be consistent with the well-established observation that, after bacterial engulfment, actin and associated proteins dissembles but are recruited again at a later stage of endocytic transit 30,53,54 . In addition to directly controlling actin polymerization, L. pneumophila also controls actin degradation at the LCV 55 and secretes RavK, an actin-targeting effector protease.…”
Section: Discussionsupporting
confidence: 87%
“…Given that LegK2 is detected on the LCV surface 1 h postinfection [16] and that VipA-derived peptides were identified at the LCV 1 h postinfection [37], it can be hypothesized that the antagonistic activities of the LegK2/ VipA effector pair can temporally control actin polymerization on the LCV to interfere with phagosome maturation and endosome recycling. Indeed, the VipA-induced actin polymerization "compensated" by LegK2 inhibition activity, or alternatively the actin polymerization inhibition activity exerted by LegK2 followed by the actin polymerization activity exerted by VipA, would be consistent with the wellestablished observation that, after bacterial engulfment, actin and associated proteins dissemble from the LCV but are recruited again at a later stage of endocytic transit [30,52,53]. In addition to directly controlling actin polymerization, L. pneumophila also controls actin degradation at the LCV [54] and secretes RavK, an actin-targeting effector protease.…”
Section: Discussionsupporting
confidence: 83%
“…Association of EHD ATPases and several of their endocytic interaction partners (e.g., syndapin and MICALlike protein 1) with retromer in domains where vesicles are being generated at EE has also been shown (Gokool et al, 2007;Naslavsky and Caplan, 2011;McKenzie et al, 2012). It was suggested that both motor pulling by different fission complexes and the force generated by the WASH-mediated nucleation of actin, are important for the budding of vesicles from EE (Derivery et al, 2009;Jia et al, 2012;Capitani and Baldari, 2021).…”
Section: Retromer Functionmentioning
confidence: 98%